Development of PjBL-based e-worksheets utilizing the kombucha bioprocess in high school biology learning - Dhiya Millatika Tohiri; Anna Rakhmawati (Research and Development in Education (RaDEn), 2024)
Worksheets are still often made in the format of questions that are done individually. Kombucha, when viewed from the characteristics of the manufacturing process, have the potential to be innovations in conventional biology technology innovation learning. This study aimed to assess the feasibility and practicality of using project-based learning electronic worksheets with kombucha bioprocess for teaching biology. The research method employed was development research using the ADDIE model, focusing on the analysis, design, and development stages. The study involved one material expert, one media expert, two biology teachers, and 33 students. Data was collected using interviews and questionnaires. The electronic worksheet was evaluated by media and material expert lecturers for feasibility and by teachers and students for practicality The results indicated that this worksheet is both feasible and practical for biology learning activities with a material validity level of 72.6% (feasible), media validity of 98% (very feasible), biology teacher response 92% (very practical) and student response 85% (very practical). The findings of this study are expected to be an inspiration for educators in compiling media for learning activities, becoming the latest and most interesting learning content innovations in project creation.